Identification of an unrecognized circRNA associated with development of renal fibrosis - Zhu, Yun; Yan, Weimin; Xu, Shuangyan; Yu, Xiaochao; Sun, Shuo; Zhang, Shaoxiong; Zhao, Ran; Tao, Jiayue; Li, Yunwei; Li, Cuie (Frontiers in Genetics, 2023)
Backgroud: Renal fibrosis is the common characteristic of chronic kidney disease. Circular RNA plays an essential role in the occurrence and development of Renal fibrosis, but its regulative mechanism remains elusive. Methods: The animal and cell model of Renal fibrosis was established, and RNA-sequencing and real-time polymerase chain reaction (qRT-PCR) experiments were implemented. Subsequently, experiments for detecting apoptosis and proliferation of cell, were carried out, and the isobaric tags for relative and absolute quantification proteomics analyses were performed accordingly. Results: It was found that a newly discovered Circular RNA (circRNA_0002158), is highly expressed in kidneys or cells with fibrosis, implying that this Circular RNA might be associated with the occurrence and development of Renal fibrosis. Subsequently, the overexpression and knockdown of circRNA_0002158 were conducted in the human kidney epithelial cell line (HK-2) cells, and the results indicated that the circRNA_0002158 could inhibit apoptosis, and promote proliferation of cells. The kidney injury-related factors, including Fibronectin and plasminogen activator inhibitor-1 (PAI-1), were decreased in HK-2 cells with overexpression of circRNA_0002158, while the results were reversed in cells with knockdown of circRNA_0002158. Finally, to explore the regulative mechanism of circRNA_0002158, the iTRAQ proteomics analyses were implemented for the cell samples with OE of circRNA_0002158 and its control, it showed that multiple genes and functional pathways were associated with the occurrence and development of Renal fibrosis. Conclusion: CircRNA_0002158 is associated with regulating Renal fibrosis, and may contribute to ameliorating the progression of Renal fibrosis in the future.